IMPLEMENTASI KEBIJAKAN PENGELOLAAN KEUANGAN DAERAH MELALUI PP NO. 24 TAHUN 2005 TENTANG STANDAR AKUNTANSI PEMERINTAHAN (Studi Kasus pada Dinas Pengelola Pendapatan Keuangan dan Aset Daerah Kabupaten Sukoharjo) - NURSIAM , NURSIAM (2011)
Nursiam. The policy implementation of local government financial trough Government Regulation (PP) Number 24 in year 2005 of Governmental Accounting Standard. (The Case Study in the Assets & Financial Management and Revenue Department of Sukoharjo District). Thesis: Master of Law, Post Graduate Program University of Muhammadiyah Surakarta. The aim of this research is to know how the implementation of the financial management policy, the level of the compliance and the obstacle of the implementation of the Governmental Accounting Standard and how the future model of the local financial management in the Assets & Financial Management and Revenue Department of the Sukoharjo District. In this research the law concept is the manifestation of the symbolic meanings of the social behaviors that showed in the interaction between them. The kind of data was the primary and secondary data. His data collection was carried out with the interview and investigation of primary and secondary of legal materials. The analysis of the data used in this research was the qualitative research carried out by using the analysis model flowed (flow the model analysis) and the interactive analysis (interactive the model of analysis). The conclusion of this research was the policy implementation of local government financial management did not yet use PP no 24/2005, but it use old District Regulations and Ministry of Human Affair (MoHA) Regulation(Permendagri) No. 13 /2006 as being changed with MoHA regulation No. 59 /2007. Furthermore BPK as a government supreme auditor use PP no.24 / 2005 for the audit regulation. The obstacle of Local Government in carrying out PP no 24 /2005 was requirement to using MoHA regulation for the basic of Local Government Financial Management for all Local Government in Indonesia. This was forced to be done; because of in Provincial level also used the MoHA regulation. The future model of the financial management better based in the regulation that was results of many regulation synchronization that as guide in the local government financial management implementation. In 2010 the Local Government of Sukoharjo issued the New Local Regulation of Financial Management number 1/2010. and Bupati Regulation Number 32 /2010 about the Accounting policy that was enacted i n August 2010, both of regulation done as the response of PP no 24/2005, consequently the Local Government of Sukoharjo should be obedient that local regulation.